HACAT CELLS AS A 2D EXPERIMENTAL DIFFERENTIATING MODEL TO ANALYZE THE EARLY BIOLOGICAL EFFECTS INDUCED BY A PSORIATIC PROINFLAMMATORY MICROENVIRONMENT: CELL PROLIFERATION, DIFFERENTIATION AND FERROPTOSIS (European Journal of Histochemistry)
HaCaT cells are spontaneously transformed keratinocytes from human epidermis that are useful for studying epithelial homeostasis and related diseases due to their proliferative and differentiating abilities. We analyzed interactions between these cells and pro-inflammatory psoriatic cytokines (TNF-alpha and IL-17A), focusing on cell proliferation and differentiation in term of intercellular junctions, and the cytoskeleton. Additionally, we examined how psoriatic cytokines contribute to susceptibility to ferroptosis, a novel cell death mechanism recently recognised in psoriatic plaques. HaCaT cells were induced to differentiate using 1.8 mM CaCl2. After four days, cells were exposed to a combination (MIX) of interleukins (IL-17A, IL-22, IL-23, and TNF-alpha) for 24 (T24) and 48 (T48) h. Proliferation was assessed through BrdU incorporation assay; ultrastructural morphology was also analyzed. Claudin 1 (CLDN-1), Zonula Occludens 1 (ZO-1), keratin (K) 10, and K14 were evaluated using immunofluorescence and western blot. We also induced ferroptosis for 24 and 48 h with 20uM erastin to evaluate cell susceptibility to MIX by analyzing the concentration of GSH (glutathione, an important antioxidant) and the ratio of GSH/GSSG (reduced glutathione/oxidized glutathione), examining membrane integrity, ATP concentration and cell availability. The biological effect induced by MIX on cell differentiation was evident after 48 h of incubation on all the considered markers. Cell proliferation progressively increased with time, but in T48 MIX-incubated samples, the proliferative activity was reduced (p<0.01). The presence of both MIX and erastin after 48 h affected mitochondrial ultrastructure, suggesting an early involvement of psoriatic cytokines also in ferroptosis mechanisms. Our experimental conditions mimic the early (de)differentiation features of psoriatic keratinocytes, indicating this model can elucidate early cellular and molecular processes during the early pathogenetic phases of psoriatic plaque organization.